Analysis of Stress Distribution Around Orthodontic Miniscrew Implant:(A 3-D Finite Element Analysis Study) - Rahma H. Al-Tayar; Hussain A. Obaidi; Ayad A. Abul-Razzak (University of Mosul, College of Dentistry, 2015)
Aims: Evaluation of the ﬆress in the bone and miniscrew displacement of 1.3 and 1.4 mm in diameter inserted in two bone models of 1 and 2 mm of cortical bone thickness at 90◦ angulation to the bone. Materials and Methods: The sample consiﬆed of 20 models which were grouped into four groups, each group included ﬁve models. The bone models of diﬀerent cortical thickness (1mm,2mm) were designed by a three dimensional Finite Element Analysis Program. The miniscrew models of 1.3 and 1.4 mm in diameter were created by the same program. Then inserting the threaded part of miniscrew in the bone block at 90°, and assigning the material properties and applying of 2N as an orthodontic force. Finally the ﬆress diﬆribution in the bone and miniscrew displacement in the diﬀerent conditions were evaluated. the results were analyzed by using ANOVA and Duncan analysis. Results: The miniscrew diameter 1.4 mm inserted in 2 mm cortical bone thickness demonﬆrated the loweﬆ bone ﬆress and miniscrew displacement than the others. Conclusions: As cortical thickness and miniscrew diameter increased the bone ﬆress reduced and less miniscrew displacement occurs.